Quatramer™ encapsulation of dual‐targeted PI3‐Kδ/HDAC6 inhibitor, HSB‐510, suppresses growth of breast cancer - Sachchidanand Tiwari; Suiyang Liu; Mohd Anees; Neha Mehrotra; Ashish Thakur; Gregory J. Tawa; Gurmit Grewal; Richard Stone; Surender Kharbanda; Harpal Singh (Wiley, 2023)
Abstract Multiple studies have shown that the progression of breast cancer depends on multiple signaling pathways, suggesting that therapies with multitargeted anticancer agents will offer improved therapeutic benefits through synergistic effects in inhibiting cancer growth. Dual‐targeted inhibitors of phosphoinositide 3‐kinase (PI3‐K) and histone deacetylase (HDAC) have emerged as promising cancer therapy candidates. However, poor aqueous solubility and bioavailability limited their efficacy in cancer. The present study investigates the encapsulation of a PI3‐Kδ/HDAC6 dual inhibitor into hybrid block copolymers (polylactic acid‐methoxy polyethylene glycol; polylactic acid‐polyethylene glycol‐polypropylene glycol‐polyethylene glycol‐polylactic acid) (HSB‐510) as a delivery system to target PI3‐Kδ and HDAC6 pathways in breast cancer cells. The prepared HSB‐510 showed an average diameter of 96 ± 3 nm, a zeta potential of −17 ± 2 mV, and PDI of ˂0.1 with a slow and sustained release profile of PI3‐Kδ/HDAC6 inhibitors in a nonphysiological buffer. In vitro studies with HSB‐510 have demonstrated substantial growth inhibition of breast cancer cell lines, MDA‐MB‐468, SUM‐149, MCF‐7, and Ehrlich ascites carcinoma (EAC) as well as downregulation of phospho‐AKT, phospho‐ERK, and c‐Myc levels. Importantly, bi‐weekly treatment of Balb/c wild‐type mice harboring EAC cells with HSB‐510 at a dose of 25 mg/kg resulted in significant tumor growth inhibition. The treatment with HSB‐510 was without any significant effect on the body weights of the mice. These results demonstrate that a novel Quatramer encapsulation of a PI3‐Kδ/HDAC6 dual inhibitor (HSB‐510) represents an approach for the successful targeting of breast cancer and potentially other cancer types.